The missing Bootstrap 5 guide : customize and extend Bootstrap 5 with Sass and JavaScript to create unique website designs - Jensen, Jeppe Schaumburg (Packt Publishing, Limited, 2022)
Make your website stand out by unlocking the full potential of Bootstrap 5 and creating efficient UIs Key Features Find out how to customize all parts of Bootstrap 5 with Sass, including working with the utility API Create a unique website using only Bootstrap 5 with Sass customization and interactive features Grasp advanced Bootstrap 5 topics related to Sass, CSS, JavaScript, and source code optimization Book Description Bootstrap is one of the world's most popular and easy-to-use frontend UI toolkits for building responsive websites, but few know how to get the most out of its vast range of components, utilities, JavaScript plugins, and other features. The Missing Bootstrap 5 Guide will help you customize Bootstrap 5 with Sass to achieve a layout that stands out from the crowd, enabling you to create something unique that doesn't look like it was created with Bootstrap. With this practical guide to Bootstrap customization, developers working with Bootstrap will be able to utilize powerful customization techniques to create websites with unique designs and exclusive features. You'll see how you can develop a visually appealing website quickly and easily by taking a hands-on approach to customizing your website using advanced features of CSS, Sass, and JavaScript. Starting with learning how the Bootstrap 5 visual style is created with Sass, you'll find out how to customize it to fit your needs while achieving the website look you want. You'll then use this knowledge to create a website using most of Bootstrap 5's components and customization with Sass and JavaScript. Finally, you'll explore various advanced Bootstrap 5 topics related to Sass, CSS, JavaScript, and source code optimization. By the end of this book, you'll be able to design and build modern, captivating, and unique websites on your own using the immense capabilities of Bootstrap 5. What you will learn Identify the most important Sass features for using Bootstrap 5 Understand the structure and content of Sass code used in Bootstrap 5 Explore customization options, colors, layout, content, forms, components, helpers, and utilities Find out how to customize, extend, and improve a website to make it unique Discover different ways of using the CSS custom properties of Bootstrap 5 Get to grips with Bootstrap 5 source code optimization Who this book is for This book is for UI designers and developers who are familiar with HTML and have prior experience with Bootstrap. Frontend as well as backend developers using Bootstrap, who don't know how to code CSS but have a solid grasp on HTML, will also find this book useful. Experienced users of the default Bootstrap files can use this book to learn all about customization and other advanced features.